Pobreza multidimensional nos municípios do Ceará: fatores condicionantes e desempenho das políticas públicas pós-Constituição de 1988 - Bezerra, Francisco Diniz (2015)
The study aimed to contribute to the understanding of the poverty phenomenon in Ceará. It sought to identify and analyze the main determinants of the prevalence of poor high contingent in the municipalities of Ceará and ascertain whether the main social policies advocated in the 1988 Federal Constitution are being effective in reducing the hardships of which stems from the multidimensional poverty. During its realization, two hypothesis were considered: 1) the main government social policies were efficient in reducing the multidimentional poverty; 2) the multidimentional poverty in Ceará is due to education area privations. After defining the concept of poverty based on the capability and basic needs approaches, it was adapted the Multidimensional Poverty Index (MPI), provided by UNDP, to measure poverty in the municipalities of Ceará, using microdata from Demographic Census Sample in 1991, 2000 and 2010. The adapted MPI was formed by four dimensions and 18 indicators. After undertaking the search, into the relevant literature, of poverty conditioning factors in Ceará, outlined up an econometric model of panel data in the linear-logarithmic type, in which the MPI represented the reality of poverty in municipalities of the state in 1991, 2000 and 2010 and six explanatory variables represented the conditioning factors. Analysis showed fall in the proportion of poor, poverty intensity and MPI, between 1991 and 2010. Knowledge access privations were the most influent factors in the MPI composition confirming hypothesis 2. Education and housing policies were efficient on reducing poverty in municipalities of Ceará. Health, labor and social security policies were not enough to decrease the privations of a larger share of Ceará people, contradicting hypothesis 1. In relation to the poverty conditional factors in Ceará, it was verified that better school infrastructure, better trained teachers, health and basic sanitation investiment, greater equality in property structure and greater productivity from economic activities contributed to MPI reduction, in opposition to a greater rural participation in the working class. Despite the progress observed between 1991 and 2010, Ceará is still a poor multidimensional state, and also holds significant number of inhabitants deprived of their basic rights granted by the Brazilian Constitution or without some basic needs service.